Hubungan Pelayanan KB dan Pemberian Konseling terhadap Hambatan dalam Pelaksanaan Program KB di Puskesmas Bajeng - Rismawati Rismawati; Arini Purnama Sari (JURNAL FISIOTERAPI DAN ILMU KESEHATAN SISTHANA, 2021)
Background: Implementation of the family planning program still faces several obstacles. Factors that cause PUS to be reluctant to participate in family planning include: In terms of service, up to now, there is still a lack of quality, as evidenced by family planning participants who stopped using contraception. As well as in terms of delivery of counseling, it puts forward rational, effective and efficient contraceptive choices. Research Objectives: to determine the relationship between family planning services and counseling on obstacles to the implementation of family planning programs in the Bajeng Community Health Center, Gowa Regency. Methods: This study used a Cross Sectional Study method. The sample in this study was PUS who did not participate in family planning. The sampling technique was purposive sampling. Data were processed using SPSS and descriptive and bivariate analysis using the chi-square test and presented in the form of a frequency distribution table. Results: This study shows that there is a relationship between family planning services and obstacles in the implementation of the family planning program where the p value is obtained. There is a relationship providing counseling to obstacles in the implementation of the family planning program where the value of p =, 000. This means that the p value <? (0.05) because the p value is less than 0.05. Conclusion: There is a Relationship between Family Planning Services and Counseling Providing Against Barriers to Implementing Family Planning Programs in the Work Area of the Bajeng Community Health Center.